2018
DOI: 10.1038/s41598-018-28898-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlled study on Gamma nail and proximal femoral locking plate for unstable intertrochanteric femoral fractures with broken lateral wall

Abstract: The gamma nail and proximal femoral locking plate (PFLP) are both used for fractures. A controlled study was performed to determine the optimal implant. To assess and analyze the clinical effects of gamma nails and PFLPs for patients with unstable intertrochanteric femoral fractures, specifically with broken lateral walls. Thirty-six patients with unstable intertrochanteric femoral fractures and broken lateral walls were treated with gamma nails or PFLPs and retrospectively studied. The clinical data were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Although the difference was not significant, higher blood loss in the PFN group could be attributed to the more frequently required open reduction with wider incision and opening fracture hematoma which led to more blood loss. Intraoperative blood loss for our PFN group was comparable to that of Han et al,[ 21 ] but considerably less in the Zhang et al’s[ 22 ] study. According to Madsen et al,[ 19 ] the DHS group lost more blood than the TSP group.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although the difference was not significant, higher blood loss in the PFN group could be attributed to the more frequently required open reduction with wider incision and opening fracture hematoma which led to more blood loss. Intraoperative blood loss for our PFN group was comparable to that of Han et al,[ 21 ] but considerably less in the Zhang et al’s[ 22 ] study. According to Madsen et al,[ 19 ] the DHS group lost more blood than the TSP group.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, in another study, 20 patients with unstable trochanteric fractures and lateral wall fractures were treated with PFN. [ 21 ] The patients started partial weight-bearing one week after surgery. Zhang et al[ 22 ] reported that using intramedullary fixation to treat unstable intertrochanteric femoral fractures was encouraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AO 31-A3.3 type intertrochanteric fractures, the fracture line involves the lateral wall of femur and the medial lesser trochanter, and the instability of the fracture end leads to a significantly higher postoperative failure rate than that of other types of fractures [22][23]. The bone mass of patients with osteoporosis is reduced, and the internal bone microstructure is damaged, resulting in loose trabecular bone and increased bone brittleness.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery treatments for trochanteric fractures have become the recommended treatment, while functional and conservative treatments are only applicable in rare cases with non-displace fractures or strictly contra-indication to surgery. Treatments with internal fixation devices, including intramedullary and extramedullary fixation devices, are widely used with advantages and disadvantages [2] Gamma nail treatment is a classic intramedullary fixation device that combines a sliding hip screw with a primary nail fit into the intra medulla cavity. Treatments with Gamma nails has been widely used internationally with several advantages reported, such as increasing stability at the fracture site, advancing healing, shortening operation time, and allowing early rehabilitation [3].…”
Section: Introductionmentioning
confidence: 99%